Component-Based Model Versus Stress-Resultant Plasticity Modelling of Bolted End-Plate Connection: Numerical Implementation. (August 2017) - Alhasawi, Anas; Guezouli, Samy; Couchaux, Maël
Abstract: This paper deals with the analysis of a steel beam-to-column bolted end-plate connection subjected to cyclic loading. The proposed model consists of an improved component-based approach that closely follows the joint behavior. The study reminds the component-based analysis and shows how to implement two proposed improvements by the use of an elasto-plastic formulation and discuss their influences on the joint behavior. The first modification concerns possible separation between the end-plate and the column flange on which it is bolted (gap effect) and the second one concerns the group of two or more than two bolt-rows (group effect). Examples are subsequently detailed for validation and highlight the robustness of the proposed model. These modifications allow to the well-known component based model a new variant that gives more accurate results and remains easy-to-implement in structural analysis programs.